Field and Synthetic Waveform Tests on Using Large‐Offset Seismic Streamer Data to Derive Shallow Seabed Shear‐Wave Velocity and Geotechnical Properties. Issue 6 (23rd June 2022) - Wege, Sebastian; Legendre, Cédric P.; Chi, Wu‐Cheng; Wang, Tan Kin; Kunath, Pascal; Liu, Char‐Shine
Abstract: Characterizing properties of marine subsurface sediment helps with siting for offshore infrastructure. Shear‐wave velocity ( V s ) provides information on the geotechnical properties of the seabed. We present our initial efforts to obtain a detailed two‐dimensional model of V s for a large‐offset multi‐channel seismic (MCS) transect collected in shallow waters across the Taiwan Strait using surface waves excited by a large volume airgun. We derived the dispersion curves of the Scholte waves along the 37.5‐km‐long transect using the phase‐shift method and then conducted multimodal inversion to obtain a V s model down to a depth of 150 m. To estimate the dynamic Poisson's ratio across the transect, we combined the V s model with a compressional wave velocity model derived from the traditional MCS semblance velocity analysis. Lastly, we approximated the seismic attenuation of the profile. Our results show a large lateral variation in shear‐wave velocity. In the north, a low‐velocity zone with shear‐wave velocities of about 150 m/s was identified, while in the south, the shear‐wave velocity was found to be 300 m/s. With synthetic data, several sensitivity tests were performed to derive optimal parameters for offshore large‐offset streamer data. We particularly focused on the depth of the streamer and source and the water depth in combination with different seabed properties. Our results show that we can robustly derive the shear‐wave velocity, along with the Poisson's ratio, using large‐offset streamer data elsewhere based on the criteria we have tested using field and synthetic data sets. Plain Language Summary: With an underwater air gun and underwater receivers, we can stimulate waves that travel through the water to the seafloor and back. At the seafloor, the wave splits into different types of waves (P‐wave, S‐wave, and Scholte wave). Previous works are mostly focused on P‐waves as S‐waves cannot travel through the water column. The Scholte wave travels along the seafloor and is sensitive to the shear properties of the top 150 m shallow sediments. By using a technique called the phase‐shift method, we can infer the S‐wave velocity from the Scholte wave. Combined with the P‐wave velocity, it can provide critical geotechnical information. We found an area with a relatively low S‐wave velocity of 150 m/s in the north and another area in the south with velocities of 300 m/s. This information can be used to weigh how and where marine constructions have to be built so that they are safe even under different environmental hazards (typhoons, earthquakes, and tsunamis). We are showing that existing data sets in shallow water can be used to estimate geotechnical properties; we further give suggestions in designing surveys to efficiently measure these wave types. Key Points: Scholte wave inferred shear‐wave velocity of shallow seabed Large‐offset seismic streamer data as a tool to derive S‐wave and P‐wave velocity simultaneously Sensitivity tests for seismic streamer data on Scholte waves using synthetic waveforms